(untitled) (Journal of the College of Basic Education, 2023)
The practice of criticism is one of the life practices that a person performs in a regular manner.continuous and in every aspect of his life, and perhaps the first monetary practices are those thatWe practice it unintentionally or without methodology, as we judge things according to their validity.or its execution in its consistency with a model of what we have in mind or its inconsistency or in its beauty oraccepted it. And other monetary provisions through which we value things and assetsautomatic evaluation until this criticism, through theorizing it and employing it in a methodology, became a form ofForms of Creativity in Evaluation and Judgment When an important subject in life is chosen, creativity is to beDescribe its existence and accompany it with judgment, evaluation and enrichment. The monetary process has been developing sinceAncient eras characterized by their association with every living creativity, so they were associated first and to this day with language.As a living being that evolves in all its forms, critical concepts evolve accordingly.What is achieved in this creative process, out of the circle of influence, into a wider and upward circle.((From being affected to the objectivity that is about to transform it into a science based on principles, specific for eachOne of the arts of literature when presenting this semi-scientific objective criticism and laying its foundations - the philosopher.. Aristotle, especially in his books (Rhetoric) and (Poetry) (1) Thus, the process of creativity remainedLiterary criticism is a source of life and development until the emergence of artistic criticism, which involved criticism that becameTheatrically, as the roots of theatrical criticism are rooted in defining the dimensions of the artistic experience.Literary theorizing the origins of artistic quality in the literary effect.The researcher believes that the criticism in the theater had started from within the life of the play, because weIf we consider, for example, the play (The Frogs) by Aristophanes, which is considered one of the most famous booksThe satirical play of the ancient Greeks provided an important model for criticism and evaluation.to reality through the political audacity of its writer and his brilliant critical acumen.